Dynamics of Escherichia coli type I‐E CRISPR spacers over 42 000 years. Issue 7 (17th January 2017) - Savitskaya, Ekaterina; Lopatina, Anna; Medvedeva, Sofia; Kapustin, Mikhail; Shmakov, Sergey; Tikhonov, Alexey; Artamonova, Irena I.; Logacheva, Maria; Severinov, Konstantin
Abstract: CRISPR‐Cas are nucleic acid‐based prokaryotic immune systems. CRISPR arrays accumulate spacers from foreign DNA and provide resistance to mobile genetic elements containing identical or similar sequences. Thus, the set of spacers present in a given bacterium can be regarded as a record of encounters of its ancestors with genetic invaders. Such records should be specific for different lineages and change with time, as earlier acquired spacers get obsolete and are lost. Here, we studied type I‐E CRISPR spacers of Escherichia coli from extinct pachyderm. We find that many spacers recovered from intestines of a 42 000‐year‐old mammoth match spacers of present‐day E. coli . Present‐day CRISPR arrays can be reconstructed from palaeo sequences, indicating that the order of spacers has also been preserved. The results suggest that E. coli CRISPR arrays were not subject to intensive change through adaptive acquisition during this time.